Differential Effects of Speech and Language Therapy and rTMS in Chronic Versus Subacute Post-stroke Aphasia: Results of the NORTHSTAR-CA Trial. (April 2022) - Zumbansen, Anna; Kneifel, Heike; Lazzouni, Latifa; Ophey, Anja; Black, Sandra E.; Chen, Joyce L.; Edwards, Dylan; Funck, Thomas; Hartmann, Alexander Erich; Heiss, Wolf-Dieter; Hildesheim, Franziska; Lanthier, Sylvain; et al.
Background & objective: Contralesional 1-Hz repetitive transcranial magnetic stimulation (rTMS) over the right pars triangularis combined with speech-language therapy (SLT) has shown positive results on the recovery of naming in subacute (5–45 days) post-stroke aphasia. NORTHSTAR-CA is an extension of the previously reported NORTHSTAR trial to chronic aphasia (>6 months post-stroke) designed to compare the effectiveness of the same rTMS protocol in both phases. Methods: Sixty-seven patients with left middle cerebral artery infarcts (28 chronic, 39 subacute) were recruited (01-2014 to 07-2019) and randomized to receive rTMS (N = 34) or sham stimulation (N = 33) with SLT for 10 days. Primary outcome variables were Z-score changes in naming, semantic fluency and comprehension tests and adverse event frequency. Intention-to-treat analyses tested between-group effects at days 1 and 30 post-treatment. Chronic and subacute results were compared. Results: Adverse events were rare, mild, and did not differ between groups. Language outcomes improved significantly in all groups irrespective of treatment and recovery phase. At 30-day follow-up, there was a significant interaction of stimulation and recovery phase on naming recovery ( P <.001). Naming recovery with rTMS was larger in subacute (Mdn = 1.91/IQR = .77) than chronic patients (Mdn = .15/IQR = 1.68/ P = .015). There was no significant rTMS effect in the chronic aphasia group. Conclusions: The addition of rTMS to SLT led to significant supplemental gains in naming recovery in the subacute phase only. While this needs confirmation in larger studies, our results clarify neuromodulatory vs training-induced effects and indicate a possible window of opportunity for contralesional inhibitory stimulation interventions in post-stroke aphasia. NORTHSTAR trial registration: https://clinicaltrials.gov/ct2/show/NCT02020421 .